Effects of Centella asiatica extract on antioxidant status and liver metabolome of rotenone‐treated rats using GC–MS. (17th October 2018) - Intararuchikul, Thidarat; Teerapattarakan, Narudol; Rodsiri, Ratchanee; Tantisira, Mayuree; Wohlgemuth, Gert; Fiehn, Oliver; Tansawat, Rossarin
Abstract: Centella asiatica has been used as a culinary vegetable or medicinal herb. In this study, the hepatoprotective effect of the standardized extract of C. asiatica (ECa233) in rotenone‐treated rats was examined using a GC–MS‐based metabolomic approach. ECa233 contains >80% triterpenoids with a ratio of madecassoside to asiaticoside of 1.5(±0.5):1. Rats were randomly divided into three groups (with six rats/group): sham negative control, rotenone positive control and the ECa233 test group. Rats in the ECa233 group received 10 mg/kg ECa233 orally for 20 days, followed by 2.5 mg/kg intraperitoneal rotenone injection to induce toxicity before being sacrificed. Metabolomic analysis showed that supplementation of ECa233 protected rat liver against rotenone toxicity. Pipecolinic acid was one of the most important metabolites; its level was decreased in the rotenone group as compared with the control. Supplementation with ECa233 before administration of rotenone raised pipecolinic acid to levels intermediate between controls and rotenone alone. The metabolomics approach also helped discover a possible new genuine epimetabolite in the present work. Antioxidant tests revealed that ECa233 inhibited lipid peroxidation and increased catalase activities in liver tissue.